KOMUNIKASI INSTRUKSIONAL GURU PADA PROSES PEMBELAJARAN SISWA TUNARUNGU JENJANG SEKOLAH MENENGAH ATAS (SMA) DI SEKOLAH LUAR BIASA (SLB) SRI MUJINAB PEKANBARU - Purnama Cicilia; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Hearing impairment is a condition where a person is not able to function athis hearing to perceive sound tool and use it to communicate, it is caused by adisturbance in the functioning of hearing either in a mild, moderate, severe and verysevere. One of the methods used to train on the development of deaf students is byusing instructional communication in the learning process. This research aims todetermine the instructional methods of communication used in the at extraordinary(SLB) Sri Mujinab Pekanbaru, knowing instructional communication media used inthe classroom, and communication barriers that occur in the learning process.This research used qualitative research methods to the presentation ofdescriptive analysis. The informan in this research were 8 teachers and 3 deafstudents at extraordinary (SLB) Sri Mujinab Pekanbaru, while the object of study isan instructional teacher communication on student learning levels deaf High Schoolin extraordinary (SLB) Sri Mujinab Pekanbaru. Data collection techniques used wereobservation, interviews, and documentation. In reaching the validity of the data inthis study, researchers used an extension of participation and triangulation.The results obtained indicate that the instructional methods used by teachersto deaf students in extraordinary SLB Sri Mujinab Pekanbaru is by using signlanguage (hand movement, body language and face expression), oral method (mouthaction and face expression), and total communication (combination between signlanguage and oral method). The instructional media used for deaf students is audiovisual(video) and visual media (picture, the original object, artificial object.Instructional communication barriers between deaf students and teachers includebarriers source barriers and obstacles communicant channel or target.Keywords : deaf students, instructional communication, special school of SriMujinab Pekanbaru